Thermal decomposition behaviors and reaction mechanism of emulsion explosive with the addition of TiH2 powders - Rong Liu; Xu-Guang Wang; Hao Wang; Quan Wang; Yang-Fan Cheng (Case Studies in Thermal Engineering)
To explore compatibility and thermal stability of the emulsion explosive added with TiH2 powders, the actions of TiH2 powders on the thermal decomposition properties, reaction product compositions of the emulsion explosives were researched by TGA-FTIR, TG-DSC, XRD and XPS. The results manifested that the adding of 7.6 μm TiH2 powders in the range of 2–8 mass% could reduce the initial decomposition temperature of the emulsion explosive and promote the thermal decomposition reaction. The apparent activation energies of pure emulsion explosive sample were 110.5 and 107.05 kJ/mol, respectively. When the addition of 7.6 μm TiH2 powders to emulsion explosive was 2 mass%, the apparent activation energy decreased to the minimum value, which were 100.1 and 95.9 kJ/mol, respectively. While the initial decomposition temperatures and the activation energies of explosive samples added with TiH2 powders with particle sizes of 33.7, 50.1 and 120.0 μm both continued to rise. Furthermore, based on the experimental results, the thermolysis mechanism of emulsion explosive added with TiH2 powders was proposed. This study is helpful to further understand the thermolysis properties and reaction mechanism of emulsion explosives containing TiH2 powders, and offer theoretic direction for the formulation optimization as well as industrial production of high-energetic emulsion explosives.